2018
DOI: 10.37358/rc.18.10.6604
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Extraction Solvent on the Active Principles Content of Portulaca Oleracea Native Species

Abstract: In this paper, a study on the influence of extraction solvent on the active principles content of purslane - Portulaca oleracea extracts was performed. For the study were used both fresh and dried plants, chopped by plant chopping machine. The following extracts were obtained and analysed in the solvent systems mentioned below: (fresh) purslane extract in Ethanol 30%, (dry) purslane extract in Ethanol 30%; (fresh) purslane extract in EtOH 70%, (dry) purslane extract in EtOH 70%; (fresh) purslane extract in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results of the syneresis test which were tested for 3 days showed that the formula being tested did not experience syneresis during storage even though it was still below 10%. But seen directly indicates the existence of separation of the two phases in the test preparation (Popescu et al, 2020).…”
Section: Syneresis Testmentioning
confidence: 90%
“…The results of the syneresis test which were tested for 3 days showed that the formula being tested did not experience syneresis during storage even though it was still below 10%. But seen directly indicates the existence of separation of the two phases in the test preparation (Popescu et al, 2020).…”
Section: Syneresis Testmentioning
confidence: 90%